2015
DOI: 10.1136/tobaccocontrol-2015-052447
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette nicotine delivery can exceed that of combustible cigarettes: a preliminary report

Abstract: Introduction Electronic cigarettes (ECIGs) aerosolize a liquid that usually contains propylene glycol and/or vegetable glycerin, flavorants, and the dependence-producing drug nicotine in various concentrations. This laboratory study examined the relationship between liquid nicotine concentration on plasma nicotine concentration and puffing behavior in experienced ECIG users. Methods Sixteen ECIG-experienced participants used a 3.3-Volt ECIG battery attached to a 1.5-Ohm dual-coil “cartomizer” loaded with 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 18 publications
3
112
1
3
Order By: Relevance
“…We observed a mean plasma nicotine boost of 33.77 ng/mL in 10 min with some individuals achieving considerably higher concentrations. This level exceeds those reported by other researchers using similar (Farsalinos et al, 2014;2015) or higher nicotine e-liquid strength (Ramôa et al, 2015) and is equivalent to that observed in tobacco smokers (Russell, 1980, Russell et al, 1975 within 5 min of finishing a cigarette. The high plasma nicotine levels are likely due to a combination of: the device used, our ad libitum vaping design, 12 h nicotine abstinence requirement and the nature of our participants.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…We observed a mean plasma nicotine boost of 33.77 ng/mL in 10 min with some individuals achieving considerably higher concentrations. This level exceeds those reported by other researchers using similar (Farsalinos et al, 2014;2015) or higher nicotine e-liquid strength (Ramôa et al, 2015) and is equivalent to that observed in tobacco smokers (Russell, 1980, Russell et al, 1975 within 5 min of finishing a cigarette. The high plasma nicotine levels are likely due to a combination of: the device used, our ad libitum vaping design, 12 h nicotine abstinence requirement and the nature of our participants.…”
Section: Discussioncontrasting
confidence: 46%
“…The high plasma nicotine levels are likely due to a combination of: the device used, our ad libitum vaping design, 12 h nicotine abstinence requirement and the nature of our participants. The Aspire Nautilus tank used here is a more advanced system with more effective nicotine delivery to the aerosol (Farsalinos et al, 2016) compared to previous studies (Farsalinos et al, 2014;2015;Ramôa et al, 2015). We also selected participants already familiar with using higher nicotine strength liquid and who had baseline salivary cotinine levels exceeding 100 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alınan nikotin, sadece içerdiği nikotin kartuşuna değil, cihazın özelliklerine ve kullanıcıya bağlı olarak değişir. e-sigaralar, sigaralara göre kullanıcıların daha fazla nikotin alımına yol açmaktadır (2) . E-sigaraların kartuşunun içindeki alkoloit sıvıda nikotin yanında propilen glikol, etanol, su, tütün çiçeği ve nane, çi-kolata, meyve gibi çeşitli tat ve kokular içeren farklı esans ve kimyasallar bulunmaktadır.…”
Section: E-sigara İçeriğiunclassified
“…Nicotine uptake through e-cigarette use depends on the nicotine concentration (mg/ml) of the e-liquid being consumed, the design of the device, the user's puffing behavior, and the user's experience with the product [31][32][33][34]. This section of the report speculates that highperformance e-cigarettes may promote higher absorption of nicotine than tobacco cigarettes.…”
Section: Effects Of Nicotine Inhalation By the E-cigarette Usermentioning
confidence: 99%